Pengaruh Social Media Marketing Intagram, Price Discount, Product AQuality, Dan Brand Trust Terhadap Loyalitas Pelanggan Skincare Prettywell Kota Kediri - Raffikah Binte Amran, Nur; Murdiyanto, Edi; Aulia Munawaroh, Nuril (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to determine the effect of social media marketing Instagram, price discount, product quality, and brand trust on customer loyalty Prettywell Skincare in Kediri City. The research method used is a quantitative method with a descriptive approach. Data collection in this study was carried out by distributing questionnaires to Prettywell Skincare customers and calculated using the SPSS Version 25 application. Data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t-test, F-test, and R2 Determination Coefficient Test. In the Validity Test, it is known that all question items (X1, X2, X3 and Y) have a significance value of 0.000 <0.05 so that each variable is declared valid. Then in the Reliability Test, each variable is declared reliable because it has a Cronbach's Alpha value> 0.60. Then in the t-test it is known that the variables of social media marketing Instagram (X1), service quality (X2), product quality (X3), and brand trust (X4) have a significance value of 0.000 <0.05 so that the four variables partially have a significant effect on customer loyalty. Then in the F-test it shows that the results of the significance value are 0.000 <0.05 which indicates that social media marketing Instagram, price discount, product quality, and brand trust have a simultaneous effect on customer loyalty of prettywell skincare in Kediri City